2014
DOI: 10.1007/s10151-014-1130-3
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescent dye during bowel surgery: Are the blood supply “guessing days” over?

Abstract: Assessing the blood supply of the bowel is a difficult task even for experienced surgeons. Laser-assisted indocyanine green (ICG) fluorescent dye angiography provides intraoperative visual assessment of blood flow to the bowel wall and surrounding tissues, allowing for modification to the surgical plan, which can reduce the risk of postoperative complications. ICG angiography was prospectively performed in a single center during a 1-year period for small bowel ischemia and left colorectal resections. ICG angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 4 publications
0
22
0
1
Order By: Relevance
“…Before performing the anastomosis, 2.5 mg of ICG dye can be injected intravenously, which is based on the doses used in most of the clinical trials . However, most studies in colorectal surgery used ICG injection doses varying from 0.2 to 0.5 mg/kg . Nevertheless, it was shown that the colorectal anastomotic perfusion could also be visualized by using a much lower and less toxic dose (2.5 mg), which is in concordance with the optimal dose used for evaluation gastroesophageal anastomotic perfusion .…”
Section: Tissue Perfusionmentioning
confidence: 84%
See 1 more Smart Citation
“…Before performing the anastomosis, 2.5 mg of ICG dye can be injected intravenously, which is based on the doses used in most of the clinical trials . However, most studies in colorectal surgery used ICG injection doses varying from 0.2 to 0.5 mg/kg . Nevertheless, it was shown that the colorectal anastomotic perfusion could also be visualized by using a much lower and less toxic dose (2.5 mg), which is in concordance with the optimal dose used for evaluation gastroesophageal anastomotic perfusion .…”
Section: Tissue Perfusionmentioning
confidence: 84%
“…One study compared the anastomotic leakage rate in perfusion detection both with and without the use of ICG fluorescence imaging, which resulted in reducing the rate from 20% to 0% . Twenty‐one clinical trials reported the use of ICG as a NIR fluorescence agent with different imaging systems in intraoperative evaluation of colorectal anastomoses . ICG was often injected after anastomotic site selection to evaluate the effect of ICG in selecting the correct anastomotic site.…”
Section: Tissue Perfusionmentioning
confidence: 99%
“…The most commonly used method for evaluating colonic perfusion is for the surgeon to observe the color change or pulsation of small blood vessels on the colon wall with their own eyes [ 11 13 ]. Sometimes, it is not easy to accurately detect minute changes in the microcirculation of the colon wall by visual observation.…”
mentioning
confidence: 99%
“…Foppa et al . report outcomes in two patients. In both cases, further proximal bowel division was undertaken and no leaks were reported.…”
Section: Perfusion Imaging In Colorectal Surgerymentioning
confidence: 92%
“…The main systems used are the Pinpoint TM system (Novadaq, Mississauga, Ontario, Canada), Firefly TM (Intuitive Surgical Inc., Sunnyvale, California, USA), SPY Elite TM Kit (LifeCell Corporation, Bridgewater, New Jersey, USA), IC-Viewâ (Pulsion Medical Systems, Munich, Germany) and D-Light (Storz, Tuttlingen, Germany). These studies represent a mix of laparoscopic [10][11][12][13][14][15][16][17] and robotic cases [18][19][20]. The largest study is a retrospective case controlled study including 402 patients [12].…”
Section: Perfusion Imaging In Colorectal Surgerymentioning
confidence: 99%